Forskningstraditioner krydser deres spor - Kvalitative og kvantitative socio-kulturelle empiriske forskningsmetoder - Henningsen, Inge; Søndergaard, Dorte Marie (Kvinder, Køn & Forskning, 2000)
The article takes up the discussion about qualitative and quantitative research methods as ostensibly incopatible approaches to empirical studies - an understanding which is broadly disseminated within a range of academic disciplines. The authors trouble this dualistic understanding through concrete discussions of methodological approaches conducted by as well qualitatively as quantitatively oriented reseachers. It is argued, that difference and potential incompatibility must be seen in relation to the metatheoretical basis for the studies and thereby in relation to the research ambitions, in which the studies are involved.